Higher Order Thinking (HOTS) Skills Assessment Model in Arabic Language Skills Learning in Madrasah - Saepurrohman, Aep; Sunarya, Yaya; Majid, Muhamad Nurkholis (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
One of the goals of learning Arabic is to master the four skills of Arabic: listening skills, speaking skills, reading skills, and writing skills. The HOTS assessment of the four skills aims for students to achieve various competencies that align with the times. These competencies include critical, creative, innovative thinking, communication skills, collaboration, and self-confidence. The five things conveyed by the government, which is the target character of students, are attached to the assessment system and are 21st-century skills. This research is a qualitative study that produces descriptive data. The type of this research is library research. The data analysis used is content analysis. The HOTS assessment of the four Arabic language skills can be carried out by aligning the forms of assessment and the HOTS thinking process dimensions: creating, evaluating, and analyzing, which are then outlined in competency achievement indicators elaboration of essential competencies.